CARDIAC SURGERYShort-term and medium-term outcomes of transapical aortic valve implantation as a single-strategy approach: one center’s experience - Čanádyová, Júlia; Mokráček, Aleš; Pešl, Ladislav; Kurfirst, Vojtěch; Šulda, Mirek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction: Transcatheter aortic valve replacement has been developed as an alternative option for surgical high-risk or inoperable patients with severe symptomatic aortic stenosis. Aim of the study was to evaluate the outcomes of patients undergoing transapical aortic valve replacement as a single-strategy option by a single-center multidisciplinary heart team. Material and methods : Between June 2009 and December 2014, 41 patients underwent transapical transcatheter aortic valve implantation (TA-TAVI) at our institution. All patients received Edwards SAPIEN balloon expandable pericardial valves (Edwards Lifesciences, Irvine, CA, USA). Our center followed a “clear transapical strategy” for all patients. Results: The mean age of the patients was 79.6 years, and the mean logistic EuroSCORE was 21.06 ± 12.82%. Fifteen patients (36.6%) underwent redo operations. Complications included stroke (n = 1), re-exploration for bleeding or cardiac tamponade (n = 4), renal failure requiring temporary hemodialysis (n = 4) and permanent pacemaker implantation (n = 3). There were no myocardial infarctions or coronary obstruction. The total 30-day mortality rate was 17.1% (7 patients). Postoperative intensive care unit stay was 4.6 ± 5.7 days, and mean hospitalization was 11.6 ± 7.2 days. Conclusions: The TA-TAVI approach provides good results in terms of early and midterm outcomes. This approach is feasible and safe for patients who have high surgical risk.